Correlates of solid waste management practices of beach resorts in Batangas - Riconalla, Ana Vee A.
Abstract. This is a descriptive study testing correlates to solid waste management (SWM)practices in selected beach resorts in Batangas. Seven class "AA" and "A" resorts participated with 254 employee respondents who served as sources of data. Computed means showed highest rated attitudes and practices. Pearson r determined relationships between specific variables of demographics, attitudes to SWM practices. The study conducted FGD to get insights into the results of the survey. Generally, respondents had "more than satisfactory" mean attitude (3.71) towards SWM. Highest means were for "managing waste for a clean environment", "waste segregation", and "proper waste disposal". In terms of extent of practice, respondents had an overall mean practice of (3.19), which was satisfactory. "Waste segregation" was practiced most, followed by "disposal" and "composting". Correlation tests were significant for number of years of operation with all the SWM practices, likewise with number of employees, to most of the SWM practices except waste disposal. "Attitudes of employees" towards SWM were particularly significant for "waste minimization" and "waste avoidance". Educational qualification was significant only for "composting" and higher resort classifications proved more significant correlations to SWM practice.